Wie sollte das Steuersystem in Deutschland reformiert werden? - Katja Rietzler; Clemens Fuest; Björn Kauder; Niklas Potrafke; Stefan Bach; Philipp Breidenbach; Roland Döhrn; Christoph M. Schmidt; Margit Schratzenstaller (Wirtschaftsdienst, 2017)
Seit langem hat es keine umfassende Reform im deutschen Steuersystem gegeben. Vor der Bundestagswahl und angesichts deutlicher und wohl auch längerfristiger gesamtstaatlicher Überschüsse werden zunehmend Vorschläge zur Entlastung der Steuerzahler gemacht. Dabei sind viele Aspekte zu berücksichtigen: beispielsweise die Frage, welche Einkommensgruppe entlastet werden sollte und welche tatsächlich durch die Vorschläge entlastet würde. Im Wesentlichen beziehen sich die Reformvorschläge auf die Einkommensteuer. Es müssen aber auch die Sozialabgaben und andere Steuerarten wie die Körperschaft-, Vermögen- und Erbschaftsteuer sowie die Energiesteuern in den Blick genommen werden. – – Some authors focus on the fact that Germany shows one of the highest tax burdens among the OECD countries. Based on their analysis, they suggest approaches to reduce the tax burden in particular for lower and medium incomes. These tax reliefs are possible, and would not compromise new public investment. But decreases in personal income tax rates mainly relieve higher income earners and are accompanied by high tax losses if the top tax rates are not increased. Alternatives are relief for social contributions or VAT. Other researchers do not look at the tax burden this way: as the income tax burden in Germany is not high from a historical perspective or by international standards, there is no case for massive tax cuts, as this would jeopardise the government's ability to act and fail to correct past shifts of the tax burden at the expense of households with low incomes. Any tax cuts should be targeted at the bottom half of the income distribution without creating any revenue shortfalls. Instead, the government would be well advised to increase its efforts to overcome the public investment backlog and ensure a well functioning civil service. Furthermore, sustainability oriented tax reforms should focus on a shift of the tax burden from taxes on labour towards environmental and wealth based taxes.
Keywords: D31; E62; H20; 330